Simulation analysis of equivalent circuit model of skin-electrode impedance for transcutaneous electrical stimulation - Joni Welman Simatupang; Wilbert Wijaya; David Tyler; Clementine Mavridis (Institute of Advanced Engineering and Science, 2021)
For more than 50 years, transcutaneous electrical stimulation method has been used to cure the spinal cord injury, stroke or cerebral palsy. This method works by activating the excitable nerves, muscle fibers by electrical current stimulation through electrode to skin interface. Electrode to skin interface requires equivalent circuit to overcome the inability of measuring the skin resistivity directly. We have learned several previous models, which are from Lawler, Moineau and Keller and Kuhn. Unfortunately, Moineau model neglects the capacitance effect, while Lawler and Keller and Kuhn include capacitive and resistive nature of skin in their equivalent circuits. Both models consisted of only one parallel RC block. Therefore, this paper presents the simulation results of the proposed equivalent circuit model using two parallel RC circuits. Simulation of the proposed model is conducted in MATLAB 2015a and compared with two previous models using certain parameters. Results show that the proposed model obtained the impedance of 10.830 kΩ when it is simulated using 100Hz frequency, for Lawler model the impedance is 5.340 kΩ and Keller and Kuhn model the impedance obtained is 6.490 kΩ. The proposed model has the refined impedance compared with other models and is expected to deliver better electrical stimulation.